2007
DOI: 10.1063/1.2796156
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of fullerite C60 with N2 molecules. An investigation by x-ray powder diffraction

Abstract: The lattice parameter a of fullerite C 60 intercalated with N 2 molecules is investigated in the temperature interval 6-295 K by x-ray diffraction. It is found that the interstitial molecular N 2 has a considerable effect on both the temperatures, T c of the orientational phase transition and T g of the orientational glass formation. Hysteresis of a(T) has been detected in the T c and T g regions, besides, the abrupt change in the volume over the region defining T c . Complete intercalation of C 60 with N 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The result of the investigations of the temperature dependence a͑T͒ in the solid solutions C 60 -O 2 as well as the published data for pure fullerite 24,26 are presented in Fig. The result of the investigations of the temperature dependence a͑T͒ in the solid solutions C 60 -O 2 as well as the published data for pure fullerite 24,26 are presented in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The result of the investigations of the temperature dependence a͑T͒ in the solid solutions C 60 -O 2 as well as the published data for pure fullerite 24,26 are presented in Fig. The result of the investigations of the temperature dependence a͑T͒ in the solid solutions C 60 -O 2 as well as the published data for pure fullerite 24,26 are presented in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…A typical HIP application is illustrated [4] by the intercalation of fullerite by inert gases such as Ar, Kr, and Xe where pressures of 170-220 MPa and temperatures of 200-500°C were used to produce intercalates Ar 1.0 C 60 , Kr 0.9 C 60 , and Xe 0.66 C 60 . Other applications of the HIP method may be found in a number of publications [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In this method, temperature and pressure cannot substantially exceed the values given above because an increase in pressure results in fullerene polymerization while an increase in temperature leads to reactions with small reactive species such as oxygen.…”
Section: Introductionmentioning
confidence: 96%
“…In compounds of C60 with H2, NH4, and CO which is obtained via gas-phase intercalation, for example, the room-temperature symmetry is fcc, with variations of the lattice parameter of less than 0.2% compared to pristine fullerite. Only a minor lattice distortion is observed in N2-intercalated C60, which is obtained at high pressure (Galtsov et al, 2007), while O2 can diffuse even at atmospheric pressure through the interstices of C60 (Assink et al, 1992), which rationalizes its observed degradability by photooxidation (Hamed et al, 1993;Katz et al, 1998). These intermolecular interstices, especially the larger octahedral ones, are large enough to accommodate also the heavier alkali ions without distortion nor expansion of the fcc lattice, and cocrystallization of alkali fullerides with ammonia leads to only minor tuning of the lattice spacing.…”
mentioning
confidence: 98%
“…No liquid fullerene phases are known, and binary phases with other molecules cannot be obtained by mixing and cooling from the molten state at arbitrary proportions. Intercalation of gas-phase molecules into solid fullerite can be achieved by application of pressure (and sometimes high temperature) to the molecular gas to aid its diffusion through the interstices of C60 crystals; this method only works, however, for rare gases, methane, or small diatomic gases (Sundqvist, 2003;Galtsov et al, 2007). On the other hand, fullerenes are moderately soluble in a number of organic solvents (Ruoff et al, 1993) and stoichiometric solvates can be obtained by precipitation or slow evaporation.…”
mentioning
confidence: 99%